A Hybrid Medium—Life (and Love) in John Ashbery’s Poetry - Bartczak, Kacper (Text Matters: A Journal of Literature, Theory and Culture, 2025)
The article focuses on the form of John Ashbery’s long poems, with a view to discussing it as a vitalist formula. Ashbery continues the American romantic vitalism by bringing it close to perspectives provided by contemporary post-secular thought. In this context, Ashbery is a poet of what the Polish post-secular scholar Agata Bielik-Robson calls “life enhanced”—a position achieved by human subjectivity that becomes conscious of its immersion in materiality, while also retaining an individuating distance from the orders of nature and death. However, given Ashbery’s American transcendentalist heritage, his is a modification of the post-secular position. In it, life is a quality of the poetic medium which develops a hybrid connecting negative transcendence, essential to Bielik-Robson’s “life enhanced,” with the immanently materialist flow of experience. On one hand, Ashbery’s hybrid mediums can be associated with the immanence of the flux of experience described in William James’s concepts of “radical empiricism.” On the other, Ashbery is also a poet of negativity that disturbs the flow of immanence—a longing for completion that is a remnant of transcendentalist models informing romantic thought. The hybrid medium of Ashbery’s long poems is a form of subjective life in which the psychological complications of the transcendence-based models—skepticism or solipsism—are modified as traces of transcendence merging with the flux of experience. The result is an environment in which material life obtains resolution, while the psychological subject recognizes its connectedness to the material habitat.